Pro Inflammatory Cytokines Profiles of Patients With Long COVID Differ Between Variant Epochs - Ravindra Ganesh; Siddhant Yadav; Ryan T. Hurt; Michael R. Mueller; Christopher A. Aakre; Elizabeth A. Gilman; Stephanie L. Grach; Joshua Overgaard; Melissa R. Snyder; Nerissa M. Collins; Ivana T. Croghan; Andrew D. Badley; et al. (SAGE Publishing, 2024)
Background: Over 30% of patients with COVID-19 have persistent symptoms that last beyond 30 days and referred to as Long COVID. Long COVID has been associated with a persistent elevation in peripheral cytokines including interleukin-6, interleukin-1β, and tumor necrosis factor-α. This study reports cytokine profiles of patients in our clinic across SARS-COV-2 variant epochs. Methods: The clinical cytokine panel was analyzed in patients with Long COVID during periods that were stratified according to variant epoch. The 4 variant epochs were defined as: (1) wild-type through alpha, (2) alpha/beta/gamma, (3) delta, and (4) omicron variants. Results: A total of 390 patients had the clinical cytokine panel performed; the median age was 48 years (IQR 38-59) and 62% were female. Distribution by variant was wild-type and alpha, 50% (n = 196); alpha/beta/gamma, 7.9% (n = 31); delta, 18% (n = 72); and omicron, 23% (n = 91). Time to cytokine panel testing was significantly longer for the earlier epochs. Tumor necrosis factor-α ( P  < .001) and interleukin 1β ( P  < .001) were significantly more elevated in the earlier epochs (median of 558 days in wild-type through Alpha epoch vs 263 days in omicron epoch, P  < .001)). Nucleocapsid antibodies were consistently detected across epochs. Discussion: When stratified by variant epoch, patients with early epoch Long COVID had persistently elevated peripheral pro-inflammatory cytokine levels when compared to later epoch Long COVID. Patients with Long COVID have similar clusters of symptoms across epochs, suggesting that the underlying pathology is independent of the peripheral cytokine signature.